PENGARUH PENGOLAHAN DAN PENYIMPANAN TERHADAP STABILITAS ASAM LEMAK OMEGA-3 PADA TELUR DAN IKAN - Nelis Imanningsih; Rossi R.S. Apriyantono; Komari Komari (Persagi, 1999)
Effect of Processing and Storage on the Stability of Omega-3 Fatty Acids in Egg and Fish.Long chain omega-3 fatty acids such as Eicosapentaenoic acid (EPA) and Docosahexaenoic acid (DHA), were very important for brain development, immunity, retina and growth of child. One of natural source of these fatty acids is fish which has been processed into variety food such as abon. The other source is modifying hen egg which potentially to be added into many kind of food after processed as egg flour. This research examine the effect of processing and storage of abon and eggs flour. The methode of this research was one-group pre post test (minimal control) and the data was prepared in tabulation. Processing in to aboon ikan make EPA lost for 10.63% and DHA 7.63%. This product was acceptable, but the stability of the fatty acids were low, EPA lost 43.8% and DHA lost by 52.4% for 4 months. The eggs prepared by our lab contained 2.5% omega-3 fatty acid. To make egg yolk flour was used Spray Drying process. This process make EPA lost 43.94% and DHA 6.20%. After storing for 4 months, egg yolk flour was very stable. Because of these reason, these products can be used to supplement fatty acids in daily diet. Eggs flour can be used in any food product to supply omega-3 fatty acid for the risk group.Keywords: omega-3 fatty acid, food processing, food storage, egg flour